Pemberdayaan Sektor Informal di Kabupaten Ponorogo - Asis Riat Winanto; Khusnatul Zulva Wafirotin (Al Tijarah, 2016)
The informal sector in Ponorogo is a controversial daily phenomenon. On the one hand, the district authorities often are not friendly to them. But, on the other hand they are used as a source of revenue for local governments through the collection of the levy and to solve the problems of employment in urban areas. However, the issue of the informal sector can not be left alone, because the day their numbers grew in number and will result in public space disruption. Based on research that has been conducted shows that the informal sector players want their empowerment so that its business can be more advanced and keep it running. Several alternative development activities expected by informal sector operators are: the procurement of wagons for businesses, entrepreneurship training, the establishment of an informal group of business operators and the ease of obtaining credit. While the research conducted related to the empowerment of the informal sector seen their empowerment by forming a group / community. The formation of a group/community is based on the desire to maintain their existence in the informal sectors. Besides, the existence of this community are expected as a forum to resolve the problems related to the informal sector. Another reason, the establishment of the community is expected to be the bridge between informal sector players and government.